Mung Bean Sprouts (Vigna radiata) Ethanol Extract on Alanine Aminotransferase (ALT) Activity and Malondialdehyde (MDA) Levels in Toluene-Induced Rats - Putu Bayu Agus S.Si; Siti Khaerunnisa M.Si; Lina Lukitasari, M.Si (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objective –This study aimed to evaluate the effect ofethanol extract from mung bean sprouts on alanine aminotransferase (ALT) activity and malondialdehyde levels in toluene-induced white rats.Methods–This research is an experimental laboratory with a research design that is post-test only control group design using 40 rats (Rattus norvegicus) which were divided randomly into 5 groups, G1 (control without toluene), G2 (900 mg/kg toluene), G3 (mung bean sprouts extract 250 mg/kg + 900 mg/kg toluene), G4 (mung bean sprouts extract 500 mg/kg + 900 mg/kg toluene), G5 (mung bean sprouts extract 1000 mg/kg + 900 mg/kg toluene). ALT measurement using spectrophotometer method. Measurement of MDA using the ELISA method. The data collected will be statistically tested with the help of SPSS with a significant (p <0.05).Results–The results of the measurement of ALT activity (p=0.972) and MDA levels (p=0.190) in each group had no significant effect (p>0.05) in each treatment.Conclusion–It can be concluded that there was no significant effect of ethanol extract of sprouts on alanine aminotransferase (ALT) activity and malondialdehyde levels in white rats (Rattus norvegicus) induced by oral toluene.